How colour similarity can make banner advertising effective: insights from Gestalt theory. Issue 6 (3rd June 2017) - Chiu, Yu-Ping; Lo, Shao-Kang; Hsieh, Ai-Yun
ABSTRACT: This study used Gestalt theory to examine the effects of colour similarity on blurring the boundary between banner advertising and web page content, as well as how colour similarity can elicit unconscious scanning behaviour and improve attitudes towards brands advertised using banner advertising at the pre-attention stage. An eye tracking device was used to record and analyse participants' eye movement, and a psychological scale was used to measure the participants' brand attitudes. The results suggested that using banner advertisements with background colours similar to those of the web page content increases the fixation time and fixation count. In addition, the results revealed that a longer fixation time and a higher fixation count increase positive attitudes towards a brand advertised in a banner advertisement. The results clarify the relationship between unconscious exposure and brand attitudes and provide physiological information relevant to e-commerce.